Unraveling the role of mitochondrial dysfunction in diabetic kidney disease: insights and interventions - Fan, Zhenliang; Luo, Puchang; Gao, Yuancheng; Ma, Hongzhen; Fan, Junfen; Sanan, Shriya; Zhang, Peipei; Lu, Keda; Xia, Hong (Frontiers in Pharmacology, 2026)
The incidence of Diabetic Kidney Disease (DKD) is rising globally, paralleling the increasing prevalence of diabetes mellitus (DM). As DM spreads worldwide, DKD becomes a significant and growing complication, challenging healthcare systems. DKD is a leading cause of end-stage renal disease (ESRD), requiring costly renal replacement therapies. Mitochondria are vital for cellular energy production via oxidative phosphorylation (OXPHOS), playing a pivotal role in DKD pathogenesis through dysfunction in energy metabolism, reactive oxygen species (ROS) generation, and mitochondrial dynamics. Emerging evidence highlights the crucial role of mitochondrial dysfunction in the pathogenesis and progression of DKD. This review elucidates the intricate relationship between mitochondrial dysfunction and DKD pathophysiology, emphasizing mechanisms such as impaired OXPHOS, excessive ROS production, and disrupted mitochondrial biogenesis. We critically analyze therapeutic interventions, including preclinical compounds, repurposed clinical drugs, and experimental molecules, highlighting their efficacy, limitations, and clinical translation challenges. Emerging evidence suggests novel mitochondrial-targeted therapies may mitigate DKD progression, though controversies, such as inconsistent PGC-1α expression, warrant further investigation. By integrating molecular insights with clinical perspectives, this review aims to guide future research and therapeutic development for DKD.